Kościół rzymskokatolicki w Polsce wobec problemu pedofilii po 1978 roku - Płachecka, Agata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The monograph is the result of long-term research into the complex nature of the sexual abuse of minors by clergy within the Polish Catholic Church. The principal aim of the work is to characterise the legal and social conditions underlying this problem, which stem from the distinctive legal status of the Church in Poland and from the fact that a clergyman who perpetrates sexual violence is simultaneously subject to two legal orders - that of the state and canon law.
Keywords: Kościół katolicki; duchowieństwo katolickie; pedofilia; wykorzystywanie seksualne małoletnich; prawo kanoniczne; konkordat; relacje państwo?Kościół; Konferencja Episkopatu Polski; ochrona dzieci; polityka i religia; Polska; 20 w.; 21 w.; paedophilia; Roman Catholic Church; clergy; sexual abuse of minors; canon law; concordat; state-Church relations; Polish Bishops` Conference; child protection; politics and religion